Analisis Kesinambungan Fiskal Indonesia Pasca Krisis Ekonomi - Muhammad Basorudin (Department of Development Economics, Universitas Sriwijaya, 2019)
The debt to Gross Domestic Product (GDP) ratio is one of the indicators used to measure fiscal sustainability in Indonesia. From 2010-2017 on a quarterly basis, the debt to GDP ratio of Indonesia contributed to an upward trend. The purpose of this research is to get a general description of the debt ratio to GDP and analyze the factors that affect the ratio of debt to GDP simultaneously and partially to be used as an early warning for the fiscal sustainability of Indonesia. The model used in this research is Error Correction Mechanism (ECM). The results obtained from this research is the Indonesia’s debt to GDP ratio is influenced by the debt to GDP ratio previous quarter. The influence given to the current quarterly debt ratio in the short run is greater than long run.